(3GdJMOjO aj GdEJbGf hGdJLhjOs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj, J (B444 (3g` s
(3ChdgG (B:s
(3bGd CHh YeQh YKeGf Hf SYjO Hf YKeGf GdebQi GdMeO ddg GdeJaQO HGdfYeGA CMeOg Ydi fYeGFg GdJi dGJNai hCdGFg GdJi dGJMUi s
(3BNQgG (B:s
(3JeJ cJGHI cJGH GdJMOjO ai GdEJbGf hGdJSOjO ai UjZI GdJLhjO HYhf Gddg Gdedc s
(3GdfSNI HgG MhGTs
(3Ydjg Jedc ddTjN GdSLGYis
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs